Immune activation of characteristic gut mycobiota Kazachstania pintolopesii on IL-23/IL-17R signaling in ankylosing spondylitis - Zhang, Haiting; Wei, Yu; Jia, Huanhuan; Chen, Diling; Tang, Xiaocui; Wang, Jian; Chen, Meili; Guo, Yinrui (Frontiers in Cellular and Infection Microbiology, 2022)
It is very important to understand the communication/interaction mechanism between the host and its resident microorganisms on host physiology and for precise diagnosis and treatment. Although intestinal fungi and bacteria dysbiosis is increasingly linked to ankylosing spondylitis (AS), their mechanism of action has been seldom illustrated. In this paper, fecal samples from 10 AS monkeys, with clinical and radiographic assessments (1), and 10 healthy controls were collected to systematically characterize the gut mycobiota and microbiota in AS monkeys by 16S rRNA and ITS2 DNA sequencing. Our results showed that the gut fungi of Kazachstania pintolopesii, Saccharomycetaceae, Kazachstania, Saccharomyceteles, Saccharomycetes were specially enriched in AS; and the microbiota of AS monkeys was characterized by an increased abundance of the Clostridia, Clostridiales, Ruminococcaceae, Prevotella 2, using Line Discriminant Analysis Effect Size. Compared to healthy controls, decreased ITS2/16S biodiversity ratios and altered bacterial-fungal interkingdom networks were observed in AS monkeys. Oral administration of K. pintolopesii activate IL-17RA pathway and induce inflammatory reaction in the colonic tissue of C57BL/6 mice, also multiple AS phenotypes including fungal and bacterial dysbiosis, immune responses of NK cells, platelets, T cells, leukocytes, and B cells activation, rheumatoid arthritis and inflammatory bowel disease. We also found the secreted products of K. pintolopesii could activate the IL-17RA pathway, induces PANoptosis of macrophage RAW264.7 cells. Much worse, the PANoptosis products could promote the proliferation and morphological changes of K. pintolopesii, which resulted in much more K. pintolopesii and severe inflammatory reaction. The characteristic fungi all these findings implied that fungal and bacterial dysbiosis have a close link to AS, and their communication/interaction indeed play an important role in autoimmune responses, and the K. pintolopesii could be a potential marker microorganism in AS although its specific mechanism is not fully elucidated.